Simulation of the Thermal Conditions of Cask with Fuel Assemblies of BN-350 Reactor for Dry Storage - Ye. T. Koyanbayev; M. K. Skakov; D. A. Ganovichev; Ye. A. Martynenko; A. A. Sitnikov (Science and Technology of Nuclear Installations)
The analysis of the thermal condition of spent FA (fuel assembly) of BN-350 reactor in a six-place cask for dry storage is presented. Simulation of the thermal condition of the cask is conducted with finite elements method using ANSYS software. Calculations of fuel temperature, fuel cladding, and assembly structural elements are the part of the safety analysis for storage of spent FA. In conclusion, the results of the thermal calculations in the cases of filling cask with argon and atmospheric air are given when the thickness of the insulation cask with concrete is 0.5 and 1 m. As a result of the calculated studies, the parameters of SNF (spent nuclear fuel) storage are determined, under which the fuel temperatures will have minimum and maximum values.